PENINGKATAN PEMBERDAYAAN EKONOMI DENGAN PEMBERIAN KETERAMPILAN MEMBORDIR PAKAIAN BAGI IBU-IBU PKK KELURAHAN CEMPAKA PUTIH TIMUR, JAKARTA PUSAT - Lenda Komala; La Diadhan Hukama (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This community service program aimed to improve economic empowerment for PKK women in East Cempaka Putih Village, Central Jakarta, through training in clothing embroidery skills. The program was initiated by the Faculty of Economics and Business, Universitas YARSI, in collaboration with PKK Working Group II as part of the implementation of the Tri Dharma of Higher Education. The training focused on enhancing participants’ practical skills in embroidery using embroidery machines, with the objective of increasing household income and encouraging the development of small-scale home-based enterprises. The methods included knowledge transfer on the importance of economic empowerment, introduction to embroidery tools and materials, and hands-on practice using embroidery machines. The program was conducted in eight meetings, and participants showed high enthusiasm and attendance throughout the sessions. Evaluation was carried out by assessing the quality of embroidered products produced by participants. The results indicated that most participants were able to operate embroidery machines and produce marketable embroidered items, demonstrating the program’s potential to support sustainable community-based economic activities.